PENGARUH E-MARKETING TERHADAP VOLUME PENJUALAN UMKM KERUPUK USEK DI KELURAHAN KASEPUHAN KABUPATEN BATANG - eko sasono; Puji Rahayu (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
At the time of the Covid 19 pandemic, the sales volume of used crackers has decreased. A strategy is needed to increase sales volume, one of which is by using E-Marketing. The population of this study was 78 people who were Entrepreneurs of Micro, Small and Medium Enterprises of Usek Crackers in Kasepuhan Village, Batang Regency. The samples used in this study were all populations, then analyzed using quantitative data analysis, including: validity and reliability tests, classical assumption tests, simple regression analysis , hypothesis testing through t test, and analysis of the coefficient of determination. The results of the study indicate that E-Marketing has a significant effect on Sales Volume. The R Square number of 0.821 indicates that 82.1 percent of the Sales Volume variable can be explained by the E-Marketing variable in the regression equation. Suggestions from the results of this study are that usek crackers SMEs entrepreneurs to further improve their marketing strategies through E-Marketing, especially in promotions or offerings of goods to be made as attractive as possible, so that potential consumers will be interested and buy usek crackers products. In finding consumers through E-Marketing sellers should increase the intensity in using social media.